Peranan HMI terhadap Pendidikan Politik Mahasiswa FISIP USU - Desi Alinda Putri Siregar (Dinamika Politik, 2013)
This study is a study of the role of HMI FISIP USU Students' Political Education. The focus of Education discusses how political methods FISIP HMI for USU students. The findings of this study include There are 4 methods of political education conducted HMI commissariat FISIP USU include: First, Formal Training; Second, Informal Training; Third, the discussion; Fourth, Action / demonstration. The method used is descriptive-qualitative method that is intended to describe an event in more detail.Keywords: Political Education, Student Organization, regeneration